A Real-World, Population-Based Retrospective Analysis of Therapeutic Survival for Recurrent Localized Renal Cell Carcinoma After Nephrectomy - Kim, Sung Han; Choi, Min Gee; Shin, Ji Hye; Kim, Young-Ae; Chung, Jinsoo (Frontiers in Oncology, 2021)
We retrospectively analyzed therapeutic strategies and risk factors for overall survival (OS) in disease recurrence following curative nephrectomy for localized renal cell carcinoma (loRCC) using the Korean National Cancer Registry Database. We selected 1295 recurrent loRCC patients who underwent either partial or radical nephrectomy from 2007–2013. Patients were excluded for age <19 years, secondary RCC, multiple primary tumors, other SEER stages except for a localized or regional stage, postoperative recurrence within 3-month, and non-nephrectomized cases. Four therapeutic groups were statistically analyzed for OS and risk factors: surgery (OP, 12.0%), other systemic therapy (OST, 59.5%), radiotherapy (RT, 2.8%), and targeted therapy (TT, 25.8%). The overall mortality rate for recurrent loRCC was 32.5%, including 82.4% for RCC-related deaths. The baseline comparison among groups showed statistical differences for the diagnostic age of cancer and the SEER stage (p<0.05). Multivariate analysis of OS showed significance for the TT (hazard ratio [HR]: 6.27), OST (HR: 7.05), and RT (HR: 7.47) groups compared with the OP group, along with significance for the sex, SEER stage, and the time from nephrectomy to treatment for disease recurrence (p<0.05). The median OS curve showed a significantly better OS in the OP group (54.9 months) compared with the TT, OST, and RT groups (41.7, 42.9, and 38.0 months, respectively; p<0.001). In conclusion, the surgery-treated group had the best OS among the different therapeutic strategies for recurrent loRCC after nephrectomy, and the importance of the time from nephrectomy to secondary treatment was a significant prognostic factor.